Short Communication: A new distribution record of the mud-spiny lobster, Panulirus polyphagus (Herbst, 1793) (Crustacea, Achelata, Palinuridae) in Mayalibit Bay, West Papua, Indonesia (Biodiversitas Journal of Biological Diversity, 2017)
Wahyudin RA, Wardiatno Y, Boer M, Farajallah A, Hakim AA. 2017. Short Communication: A new distribution record of the mud-spiny lobster, Panulirus polyphagus (Herbst, 1793) (Crustacea, Achelata, Palinuridae) in Mayalibit Bay, West Papua, Indonesia. Biodiversitas 18: 780-783. Panulirus polyphagus (Herbst 1793) (Crustacea, Decapoda, Achelata, Palinuridae) from Waigeo Island is illustrated and described in detail of morphological characters. This species is reported as new distribution record from Mayalibit Bay, Raja Ampat District, Province West Papua, Indonesia. One specimen was collected by local fisherman from muddy substrate waters at a depth of 10-40 m. The collection was made in June 2016. The present study adds more distribution of species in the world and enhances the marine diversity of Indonesian crustacean lists. Some brief biological information on the species is presented.
Keywords: Crustacean diversity; morphological description; Waigeo Island; new record; Pakistan lobster